In vivo administration of azithromycin affects lymphocyte activity in vitro. - Tomazic, J (1993)
A therapeutic dose of azithromycin was administered to test subjects and then the following lymphocyte functions were examined in vitro: proliferative lymphocyte response to stimulation with pokeweed mitogen, levels of immunoglobulins G, A, and M in serum, and the amount of the soluble interleukin 2 receptors in supernatants of mononuclear cell cultures stimulated with phytohemagglutinin and phorbol myristate acetate. The study was performed as a controlled clinical trial comparing an azithromycin-treated group (n = 21) and a placebo-treated control group (n = 10). Healthy female volunteers were placed into one of the two groups, and the study was performed as a double-blind trial. Although the findings of the present study showed that azithromycin significantly increased the proliferative lymphocyte response to pokeweed mitogen, the results could have been due to experimental variation. However, impairment of the lymphocyte function was not observed, which could represent valuable information. Likewise, no effect of azithromycin on levels of the immunoglobulins in serum was observed. The most marked effect of azithromycin on the lymphocyte function was demonstrated by an elevation in the amount of soluble interleukin 2 receptor production in mononuclear cell cultures. The lack of impairment or, perhaps, even a beneficial influence on the immunodefense system may be an important property of azithromycin, especially in immunocompromised individuals.